Cheer* in Health Care Practice: What It Excludes and Why It Matters. (November 2019) - Setchell, Jenny; Abrams, Thomas; McAdam, Laura C.; Gibson, Barbara E.
Clinicians' positive demeanor and "strengths based" focus can include working to create a cheerful atmosphere in health care environments, cheering for improvements in assessment outcomes, and cheering up clients in situations of decline. Drawing from philosopher Karen Barad's theories of inclusions and exclusions, we investigated what comes to matter (and what is excluded from mattering) when there is cheerfulness, cheering, and so forth (cheer*) in the day-to-day practices of a neuromuscular clinic. We worked collaboratively with clinicians, young people with Duchenne muscular dystrophy, and their families to co-examine the clinic in three iterative exploratory method spaces: (a) group "dialogues" with clinicians; (b) consultative interviews with children, families, and clinicians; and (c) transdisciplinary research team analysis sessions. Cheer* made some things matter in the clinic ("normal" physical function, "positive" emotions, test scores, compliance); and excluded others (grief and loss, "non-normative" bodies and lives, alternative practices, embodied knowledge). We discuss implications across health care settings.